Ukrainian Social Elite in Pylyp Orlyk’s Lliterary Works - Larysa Lytvyn (Вісник Харківського національного університету імені В. Н. Каразіна. Серія Філологія. Vìsnik Harkìvsʹkogo nacìonalʹnogo unìversitetu ìmenì V.N. Karazìna. Serìâ Fìlologìâ.)
The principal focus of the article is the determination of the circle of Ukrainian elite representatives and the examination of the means of their image features, that are used by the prominent Ukrainian hetman in exile as well as baroque literator Pylyp Orlyk. His poetry collections "Ruthenian Alcide" and "Sarmatian Hippomenes", in addition to several insignificant eulogies, which were published in the course of the "Mazepian era", united the military, religious and cultural elites around the hetman. Poltava tragedy, which was fatal for Ukraine and personally for Pylyp Orlyk, divided Ukrainian elites into exiled ones and Russian supporters. His life-driving perspective about the current circumstances is described in his letters aimed at Ukrainian elites in Russia and Western Europe. Orlyk`s "Blank diariush" was journaled within the period from 1720 to 1733 and reflects the fluctuations of the author`s mood, the circle of people, that is entrusted with the mission of state foundation by Pylyp Orlyk, along with genre and artistic preferences of his creations.